Massive hemoptysis as the sentinel symptom: a case report of pulmonary nocardiosis in an immunocompetent patient - Zhang, Qiuping; Gong, Qiangjin; Sun, Xiaokui; Zhu, Huizhi (Frontiers in Medicine, 2025)
Pulmonary nocardiosis is frequently missed or misdiagnosed due to its atypical clinical symptoms and non-specific imaging findings. Moreover, delayed diagnosis and treatment can lead to high mortality rates, underscoring the need to enhance etiological diagnosis. Here, we report a 55-year-old immunocompetent woman who developed pulmonary Nocardia cyriacigeorgica infection with massive hemoptysis as the initial symptom. The patient had no history of chronic respiratory diseases. Metagenomic next-generation sequencing of bronchoalveolar lavage fluid collected via bronchoscopy was performed, which confirmed the diagnosis. After targeted therapy with oral sulfamethoxazole-trimethoprim and linezolid, the patient achieved significant symptomatic and radiological improvement, accompanied by normalization of white blood cell count and neutrophil count. No recurrence was observed during follow-up.